The Principal's Strategy In Increasing Student Competitiveness Through Spiritual Quotient - Moh. Anwar; Imron Fauzi (At-Tarbiyat, 2024)
This study aims to analyze the principal's strategy in applying students' spiritual intelligence (SQ: Spiritual Quotient) values and their impact on student competitiveness in the world of work. Through qualitative research methodology with a case study approach in a secondary school, this research identifies concrete steps taken by the principal to integrate spiritual intelligence in the educational environment. At the implementation strategy stage, the headmaster focuses attention on developing a spiritual intelligence-based curriculum, structured character building programs, in-depth training for teachers, creating a supportive school environment, and monitoring continuous evaluation. Furthermore, in-depth research is conducted on the impact of the application of this spiritual intelligence on students' competitiveness in the world of work, including the development of soft skills, integration into educational programs, cooperation with the corporate world, career program development, impact measurement through alumni, and the awarding of certificates or awards. The results show that these strategies have positive implications on students' character growth and prepare them holistically for challenges in the world of work. These findings contribute to principals, teachers, and researchers in understanding the principal's key role in shaping an educational environment that supports students' spiritual development and competitiveness in today's global era